Complications In The Management Of High-Energy Closed Fractures Of Proximal Tibial Plateau. A Retrospective Study - Rahman Rasool Akhtar; Waqas Ali; Riaz Ahmed; Muhammad Nadeem Kashmiri; Hira Waris; Muhammad Haider (Journal of Rawalpindi Medical College)
Objective: To analyze the management of high-energy Schatzker type V and VI tibial plateau fractures which are associated with infectious and noninfectious complications.